Evaluating the Effect of Milling Time on the Microstructural Changes and Phase Analysis of Mg-3Zn Powder Synthesized by Mechanical Alloying - M. Yahyazameh; M. Kavanlouei; M. Shahbaz; Y. Beygi-Khosrowshahi (Journal of Advanced Materials in Engineering)
In this study, Mg-3Zn nanocomposite powder was produced using planetary ball mill under argon atmosphere. The aim of this work was to study the effect of milling time (2.5, 5, 7.5, and 10 h) on the crystallographic features and microstructure of Mg-3Zn. X-Ray diffraction (XRD) was used to investigate phase analysis of various milled powders. Also, the morphology of different samples were observed by scanning electron microscopy (SEM). The crystallographic features of the composite powders such as crystallite size, strain, and lattice parameter were thoroughly characterized by Rietveld and Williamson-Hall methods. The effect of milling time on the mechanical properties of the powders was evaluated using microhardness test. The results declared that crystallite size, lattice parameter, and microhardness of Mg-Zn powder decreased with increasing milling time.